I remember Beirut - Abirached, Zeina, 1981- (Graphic Universe, 2014)
"Abirached was born in Lebanon in 1981. She grew up in Beirut as fighting between Christians and Muslims divided the city streets. Follow her past cars riddled with bullet holes, into taxi cabs that travel where buses refuse to go, and on outings to collect shrapnel from the sidewalk. With striking black-and-white artwork, Abirached recalls the details of ordinary life inside a war zone"--